The interaction between tobacco use and oral health among tribes in central India - Khanna, Sunali (BioMed Central, 2012)
BACKGROUND: A study was undertaken to evaluate the effect of tobacco related practices on oral health of tribes in Central India. The use of smokeless tobacco, gutkha & associated products is on the rise amongst the younger generation making oral precancer & cancer a public health concern. METHODOLOGY: A pioneering study was conducted to evaluate the tobacco related practices amongst tribes and its impact on oral health. The study included 411 tribals of the Baiga group. Guided dialogue techniques and proforma based evaluation formed a part of the study. RESULT: 53.04% of individuals between 21 to 40yrs are addicted to deleterious habits. There is a marked consumption (72%) of tobacco & associated products among the geriatric population (60 yrs & above).Insecure livelihoods, malnutrition & increased stress levels contribute to the stark increase of addiction of tobacco related practices. CONCLUSION: The healthcare infrastructure needs to be upgraded to meet the demands of changing disease profile amongst the vulnerable population. Assessment of impact of disease on existing public health would enable formulation of adaptive measures and suggestions for amelioration.